Un commentaire sur l'article de E. Niesten et R. Rice les (concessions de conservation) sonnent-elles le glas de l'amenagement forestier durable? - Karsenty, A.; Nasi, Robert (2004)
Conservation concessions, as advocated by E.Niesten and R.Rice, suggest the paying revenues to populations and the State so that they may renounce income derived from forest exploitation. Apart from the questionable transformation of peasants as renters of conservation, serious questions arise as regards the assessment of financial compensation; the hypothesis of repurchase of traditional rights through contracts is barely realistic. Similarly, the argumentation with regard to sustainable management or the underlying economic pattern is not fault-free. In the event that environmental concessions do not constitute a global alternative to logging, the conditions of their use as complementary instruments to already existing ones remains to be defined.